Towards a strategy to zero energy buildings (ZEB) concept - Goncalves, Helder (2010)
The energy consumption in buildings and the need for its reduction has been since the late 60’s and 70ś a main question among professionals (designer, architects, and engineers), legislators and users around the word. Reduction in energy demand for heating for instance was implemented in the so called Solar Buildings (with reduction of 70 to 80% in the heating demand). The building regulation start putting targets, in the overall annual energy consumption xx kWh/m2 year, and some achieve the level of standards, imposing very low values, such as Passivhaus standard which fundamentally consists of an energy limit (net useful energy demand for heating of 15 kWh/m²/year and a total primary energy consumption of 120 kWh/m²/year). Now we are dealing for a new concept, in which those values approach zero (ZEB) or even minus, which correspond to building which produce more than what they spend (ENERGY PLUS BUILDINGS). This paper discusses some of the main issues regarding the strategy to achieve some of these goals in the future.